2011
DOI: 10.1007/s12272-011-0113-4
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinase-13 expression in IL-1β-treated chondrocytes by activation of the p38 MAPK/c-Fos/AP-1 and JAK/STAT pathways

Abstract: Matrix metalloproteinase-13 (MMP-13, mammalian collagenase) degrades the cartilage matrix in pathological conditions such as osteoarthritis. Here, to establish the signaling pathway to MMP-13 induction, effects of mitogen-activated protein kinase (MAPK) pathway and the possibility of some other signaling pathways involved are investigated in interleukin-1β (IL-1β)-treated human chondrosarcoma cell line, SW1353 cells. IL-1β (10 ng/mL) treatment induced MMP-13 in SW1353 cells, with concomitant activation of nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
56
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(63 citation statements)
references
References 34 publications
7
56
0
Order By: Relevance
“…In particular, STAT1/2 activation is involved in IL-1β-treated SW1353 cells (21). When the cells were treated with apigenin, STAT1/2 activation was considerably inhibited in a concentration-dependent manner (Fig.…”
Section: Effects Of Apigenin On the Jak/stat Signaling Pathwaymentioning
confidence: 89%
See 2 more Smart Citations
“…In particular, STAT1/2 activation is involved in IL-1β-treated SW1353 cells (21). When the cells were treated with apigenin, STAT1/2 activation was considerably inhibited in a concentration-dependent manner (Fig.…”
Section: Effects Of Apigenin On the Jak/stat Signaling Pathwaymentioning
confidence: 89%
“…From the same media, MMP-13 expression was also examined by Western blotting analysis. The optimum expression time of MMP-13 and other signaling molecules was determined in the previous study (21). In brief, media was concentrated with TCA and acetone.…”
Section: Sw1353 Cell Culture and Mmp-13 Inductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The p38 MAPK/c-Fos/AP-1 and JAK2/STAT1/2 pathways are involved in MMP-13 induction in IL-1β-treated HTB94 human chondrocytes. Blocking these signaling pathways may have chondroprotective effects in cartilage degeneration (27). Another study demonstrated downregulation of MMP-13 by the root extract of Cyathula officinalis Kuan and its constituents in IL-1β-treated chondrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…33 MMP-13 expression in chondrocytes also is modulated by the c-Jun N-terminal kinase and NFkB signaling pathways. 34 Previous studies have shown that SAHA selectively attenuates mitogen-activated protein kinase and NF-kB signaling activity in IL-1beinduced human OA chondrocytes.…”
Section: Discussionmentioning
confidence: 99%